Assessment of the oncological outcomes of three different bacillus Calmette–Guérin strains in patients with high-grade T1 non-muscle-invasive bladder cancer. Issue 1 (2nd January 2021) - Nowak, Łukasz; Krajewski, Wojciech; Moschini, Marco; Chorbińska, Joanna; Poletajew, Sławomir; Tukiendorf, Andrzej; Muilwijk, Tim; Joniau, Steven; Tafuri, Alessandro; Antonelli, Alessandro; Orlando, Rossella; Di Trapani, Ettore; et al.
ABSTRACT: Objective: : To determine whether there are significant differences in oncological outcomes between three different bacillus Calmette–Guérin (BCG) strains used for adjuvant intravesical immunotherapy in patients with high-grade T1 (T1HG) non-muscle-invasive bladder cancer (NMIBC). Patients and methods: : Data of 590 patients with a diagnosis of primary T1HG NMIBC were retrospectively reviewed. The study included 138 (23.4%) patients who were treated with the Moreau, 272 (46.1%) with the TICE, and 180 (30.5%) with the RIVM strains. All patients included in the analysis received at least five instillations of an induction course and at least two installations of a maintenance course. Due to existing differences in baseline patient characteristics, the association between oncological outcomes and strain groups was investigated by complementary analysis with the implementation of inverse probability weighting (IPW). Results: : The 5-year recurrence-free survival (RFS) rate was 70.5%, 66.7% and 55.2% for the Moreau, TICE and RIVM groups, respectively ( P = 0.016). The 5-year progression-free survival (PFS) rates were 84.4%, 85% and 77.8% in the Moreau, TICE and RIVM groups, respectively ( P = 0.215). The IPW-adjusted Cox proportional hazard regression analysis did not show any differences in RFS between the Moreau and TICE groups ( P = 0.69), whereas the RIVM strain was significantly associated with worse RFS compared to the Moreau (hazard ratio [HR] 1.69 for RIVM; P = 0.034) and TICE (HR 1.87 for RIVM; P = 0.002) strains. The IPW-adjusted analysis did not show any significant differences between study groups in terms of PFS. Conclusions: : The results of the present study suggest that the Moreau and TICE strains might be superior to the RIVM strain in terms of RFS in patients with T1HG NMIBC. Abbreviations: CIS: carcinoma in situ ; IPW: inverse probability weighting; IQR: interquartile range; HR: hazard ratio; HG: high grade; LVI: lymphovascular invasion; MP: muscularis priopria; NMIBC: non-muscle-invasive bladder cancer; PFS: progression-free survival; RCT: randomised controlled trial; RFS: recurrence-free survival; T1HG, high-grade T1; (re-)TURB: (re-staging) transurethral resection of bladder; VH: variant histology